AN ANALYSIS OF ENGLISH LANGUAGE POLITENESS USED BY THE LOCAL TOUR GUIDE OF BELUMBANG TOURISM VILLAGE IN TABANAN, BALI - Widhiastuty, Ni Luh Putu Sri; Junipisa, Made Ernila; Trianingrum, Ni Nyoman Nidya (Program Studi Pendidikan Bahasa Indonesia dan Daerah Universitas PGRI Mahadewa Indonesia, 2025)
The purposes of the research were to study and to analyze English Language Politeness used by the local tour guides of Belumbang Tourism Village in Tabanan, Bali. The approach used is a qualitative method with a phenomenological approach, which allows an in-depth understanding of the behaviour of tour guides in communicating with tourists. The research data was collected through questionnaires completed by respondents as well as structured interviews with key informants, who provided first-hand views of communication practices in the tourism context. The collected data were analysed using a qualitative descriptive method, with reference to the theory of language politeness developed by Leech (1983), which includes six language politeness maxims: (1) Tact Maxim, (2) Generosity Maxim, (3) Approbation Maxim, (4) Modesty Maxim, and (6) Sympathy Maxim. The research shows that local tour guides in Belumbang Tourism Village consistently apply the six maxims in daily interactions, both in providing information and services to tourists. This reflects a high level of language politeness, which is crucial in creating a positive tourism experience, strengthening interpersonal relationships, and maintaining local cultural values.